A case of probable Amiodarone-induced pancreatitis in the treatment of atrial fibrillation: a literature review and case report. Issue 6 (24th November 2017) - J. Mercogliano, Christopher; Khan, Muhammad; Ahmad, Mussaber
ABSTRACT: Amiodarone is an effective medication used in the treatment of several different arrhythmias. Its most well-known adverse effects include pulmonary fibrosis, thyroid dysfunction, and hepatotoxicity. A less common side effect is acute pancreatitis. A 67-year-old male being treated for atrial fibrillation in rapid ventricular response with Amiodarone developed acute epigastric abdominal pain 24 hours after initiation of therapy. He was diagnosed as having acute pancreatitis based on characteristic findings seen on an abdominal CT scan. Commonly encountered etiologies of pancreatitis were ruled out through a combination of the history, laboratory values, and imaging results. Based on the temporal association of the acute presentation and initiation of Amiodarone therapy, in conjunction with a lack of support for any other etiology, the diagnosis of Amiodarone-induced pancreatitis was made. Within 7 days following the cessation of Amiodarone therapy, the patient's symptoms had completely resolved. Amiodarone-induced pancreatitis is an often overlooked medication association and is one that has been infrequently reported throughout the literature. Given the substantial morbidity and mortality associated with acute pancreatitis, and the ease of treatment (withdrawing Amiodarone), this is a critical side effect that should be recognized in the appropriate clinical setting.